Sex and age differences in chronic postoperative pain among patients undergoing thoracic surgery: a retrospective cohort study - Zhao, Ying; Liu, Xin-Min; Zhang, Lu-Yao; Li, Bing; Wang, Ruo-Han; Yuan, Qin-Yue; Wang, Shi-Chao; Zhu, Hai-Peng; Zhi, Hui; Zhang, Jia-Qiang; Zhang, Wei (Frontiers in Medicine, 2023)
Background The effect of sex and age on chronic post-thoracic surgical pain (CPTP) at rest and with activity remains unclear. The main purpose of this study was to investigate the relationship between the incidence of chronic postoperative pain (at rest and with activity) and sex/age differences. Methods This was a single-center retrospective study that included adult patients who had undergone elective thoracic surgery. Patients were divided into two groups based on sex. Demographic and perioperative data were collected, including age, sex, education level, Body Mass Index (BMI), American Society of Anesthesiologists (ASA) physical status, and medical history (hypertension, diabetes mellitus). Chronic postoperative pain data were collected by telephone follow-up. Results Among the 3,159 patients enrolled, 1,762 were male, and 1,397 were female. After creating a matched-pairs cohort, 1,856 patients were analyzed. The incidence of CPTP at rest was 14.9% among males and 17.8% among females (p = 0.090). The incidence of CPTP with activity was 28.4% among males and 35.0% among females (p = 0.002). We analyzed three different models after propensity matching to validate the stability of the prediction model between sex and CPTP, and female sex was a significant predictor of CPTP with activity 3 months after surgery. Further analysis showed that females in the 45-55-year-old age group were more prone to develop CPTP. Conclusion Females have a higher incidence of chronic postoperative pain with activity after thoracic surgery. Females in the 45-55-year-old age group are more prone to develop CPTP than females in other age groups.